Cognitive Maps of the Beliefs of Pre-service Mathematics Teachers Regarding Mathematics: A Phenomenological Research - Katmer-Bayrakh, Vildan; Erisen, Yavuz (GATE ASSOC TEACHING & EDUCATION-GATE, SWITZERLAND, 2019)
This study investigates the beliefs of pre-service mathematics teachers (PMTs) regarding mathematics through plotting their cognitive maps. The PMTs' beliefs regarding the nature of mathematics, and teaching and learning mathematics were considered in depth using a phenomenological approach. Participants in the study were seven PMTs in the fourth year of the Elementary School Mathematics Education Program at a university in Istanbul. Data were collected through individual interviews and analyzed by plotting cognitive maps. The results showed that all PMTs had similar cognitive maps of beliefs regarding mathematics. Although the PMTs stated that they held traditional (teacher centered) beliefs before enrolling in the teacher-training program, they demonstrated that they held more constructivist beliefs as a result of the teacher-training program. The use of cognitive maps was shown to be effective in providing a holistic examination of the beliefs of PMTs and a comparison of their belief systems.
Keywords: beliefs; cognitive maps; pre-service mathematics teachers; phenomenology; qualitative research; ELEMENTARY MATHEMATICS; Education & Educational Research